Pendalaman Buku Ajar Elektrikal dan Elektronika Pesawat Udara Bagi Guru SMK Penerbangan - Sihono, Sihono; Fatkhulloh, Amal; Saputro, Riyanto; Herwanto, Djoko; Kalbuana, Nawang (Jurnal Pengabdian Kepada Masyarakat, 2021)
As one of the roles of universities in realizing Tridharma Higher Education, especially in the field of Aviation, The Indonesian Aviation Polytechnic is considered necessary to conduct socialization related to the Deepening of The Teaching Book of Electrical &Electronic Aircraft for Vocational Teachers of Aviation. This community service aims to provide knowledge, especially teachers in vocational schools related to the Book of Electrical Teaching &Amp; Electronics Aircraft it is because the readiness of teachers and teaching materials become the initial benchmark of the success of the student learning process and teaching. The current condition of many vocational school teachers is not a graduate of aviation vocational school, not a graduate of a campus that organizes education in the field of aviation, inexperienced in aircraft maintenance or even unlicensed aviation technicians. The results of this community service show that the knowledge in the field of aviation, mostly vocational school teachers in Semarang, Solo and Surakarta is still weak. Many still deliver teaching materials to students based on the search process on the internet page without understanding the basic philosifi of its functions and work. Especially for electrical materials and aircraft electronics, there is still a condition of teachers conveying the concept of electrical components and general electronics but have not been able to connect how the components function and work in the aircraft. PKM activities deepening the teaching book of Electrical &Electronic Systems aircraft in smk reopen the role of related parties in order to improve the quality of vocational school teachers in general in the field of aviation. Pkm activities are expected to be continued in a more structured form can be in the form of cooperation partners between vocational higher education institutions in the field of aviation and vocational education (vocational education at the intermediate level).